Strategies for High-Efficiency Mutation Using the CRISPR/Cas System - Feng, Shuying; Wang, Zilong; Li, Aifang; Xie, Xin; Liu, Junjie; Li, Shuxuan; Li, Yalan; Wang, Baiyan; Hu, Lina; Yang, Lianhe; Guo, Tao (Frontiers in Cell and Developmental Biology, 2022)
Clustered regularly interspaced short palindromic repeats (CRISPR)-associated systems have revolutionized traditional gene-editing tools and are a significant tool for ameliorating gene defects. Characterized by high target specificity, extraordinary efficiency, and cost-effectiveness, CRISPR/Cas systems have displayed tremendous potential for genetic manipulation in almost any organism and cell type. Despite their numerous advantages, however, CRISPR/Cas systems have some inherent limitations, such as off-target effects, unsatisfactory efficiency of delivery, and unwanted adverse effects, thereby resulting in a desire to explore approaches to address these issues. Strategies for improving the efficiency of CRISPR/Cas-induced mutations, such as reducing off-target effects, improving design and modification of sgRNA, optimizing editing time and temperature, choice of delivery system, and enrichment of sgRNA, are comprehensively described in this review. Additionally, several newly emerging approaches, including the use of Cas variants, anti-CRISPR proteins, and mutant enrichment, are discussed in detail. Furthermore, the authors provide a deep analysis of the current challenges in the utilization of CRISPR/Cas systems and the future applications of CRISPR/Cas systems in various scenarios. This review not only serves as a reference for improving the maturity of CRISPR/Cas systems, but also supplies practical guidance for expanding the applicability of this technology.